Reproductive Phenology of Frogs in Wetlands of the Tropical Dry Forest of Costa Rica - Mora, Gabriela (2012)
Seasonal wetlands in the dry environments of Pacific Costa Rica are extremely important in maintaining high biological diversity. They constitute the main breeding sites of most amphibians and several species of reptiles that characterize the seasonal or dry forest. In an attempt to determine the importance of these wetlands in the transfer of matter and energy between aquatic and terrestrial habitats, this study describes the reproductive phenology of the community of anurans that use seasonal wetlands of Palo Verde National Park, located in the lower basin of the Rio Tempisque. From May 2009 to February 2010 we monitored the anurans that use seasonal wetlands using drift fences and pitfall traps. Thirteen species of anurans were observed using this habitat. Secondary productivity was determined by estimating wet biomass of recently emerged frogglets produced at the wetlands. Adult males and females of most species emerge from estivation sites during the onset of the rainy season (May-July), moving from the mountain to the wetland. During this period, adults are observed foraging in the woods and around the wetland, where they wait for ponds and puddles that are form with the first rains. At that time, they move to their oviposition sites. In most species, recently metamorphed frogglets emerge synchronously between the months of July-August, and continue their life cycle on the forest. During the studied breeding season a total of 6,730 g/day was produced in 300 m of the wetland perimeter. This measure represents close to a ton of amphibian biomass produced along the perimeter of this single lagoon. This approach constitutes a novel way to assess the ecological importance of wetlands and the possible implications that wetland loss could have on the surrounding ecosystems.